![image](https://tex.z-dn.net/?f=%5Clog_%7B0.2%7D%28x-2%29%2B%5Clog_%7B0.2%7Dx%3E%5Clog_%7B0.2%7D%282x-3%29%5C%5C%0A%5Cleft%5Clbrace%5Cbegin%7Barray%7D%7Bl%7D%0A%5Clog_%7B0.2%7Dx%28x-2%29%3E%5Clog_%7B0.2%7D%282x-3%29%5C%5C%0Ax%3E2%0A%5Cend%7Barray%7D%5Cright.%5C%5C%0A%5Cleft%5Clbrace%5Cbegin%7Barray%7D%7Bl%7D%0Ax%5E2-2x%3C2x-3%5C%5C%0Ax%3E2%0A%5Cend%7Barray%7D%5Cright.%5C%5C%0A%5Cleft%5Clbrace%5Cbegin%7Barray%7D%7Bl%7D%0Ax%5E2-4x%2B3%3C0%5C%5C%0Ax%3E2%0A%5Cend%7Barray%7D%5Cright.%5C%5C%0A%5Cboxed%7Bx%5Cin%282%2C3%29%7D)
\log_{0.2}(2x-3)\\
\left\lbrace\begin{array}{l}
\log_{0.2}x(x-2)>\log_{0.2}(2x-3)\\
x>2
\end{array}\right.\\
\left\lbrace\begin{array}{l}
x^2-2x<2x-3\\
x>2
\end{array}\right.\\
\left\lbrace\begin{array}{l}
x^2-4x+3<0\\
x>2
\end{array}\right.\\
\boxed{x\in(2,3)}" alt="\log_{0.2}(x-2)+\log_{0.2}x>\log_{0.2}(2x-3)\\
\left\lbrace\begin{array}{l}
\log_{0.2}x(x-2)>\log_{0.2}(2x-3)\\
x>2
\end{array}\right.\\
\left\lbrace\begin{array}{l}
x^2-2x<2x-3\\
x>2
\end{array}\right.\\
\left\lbrace\begin{array}{l}
x^2-4x+3<0\\
x>2
\end{array}\right.\\
\boxed{x\in(2,3)}" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=%5Cleft%5Clbrace%5Cbegin%7Barray%7D%7Bl%7D%0A2%5E%7B%5Clog_2%28x%2By%2B1%29%7D%3Dx%5E2%2By-1%5C%5C%0A%5Clog_%7B%5Csqrt%7B29%7D%7D%28y%5E2%2B2x%29%3D2%0A%5Cend%7Barray%7D%5Cright.%5C%5C%0A%5Cleft%5Clbrace%5Cbegin%7Barray%7D%7Bl%7D%0Ax%2By%2B1%3Dx%5E2%2By-1%5C%5C%0Ax%2By%2B1%3E0%5C%5C%0Ay%5E2%2B2x%3D29%0A%5Cend%7Barray%7D%5Cright.%5C%5C%0A%5Cleft%5Clbrace%5Cbegin%7Barray%7D%7Bl%7D%0Ax%5E2-x-2%3D0%5C%5C%0Ay%5E2%3D29-2x%5C%5C%0Ax%2By%2B1%3E0%0A%5Cend%7Barray%7D%5Cright.%5C%5C%0A%5Cleft%5Clbrace%5Cbegin%7Barray%7D%7Bl%7D%0A%5Cleft%5B%5Cbegin%7Barray%7D%7Bl%7D%0Ax%3D2%5C%5C%0Ax%3D-1%0A%5Cend%7Barray%7D%5Cright.%5C%5C%0Ay%5E2%3D29-2x%5C%5C%0Ax%2By%2B1%3E0%0A%5Cend%7Barray%7D%5Cright.%0A)
0\\
y^2+2x=29
\end{array}\right.\\
\left\lbrace\begin{array}{l}
x^2-x-2=0\\
y^2=29-2x\\
x+y+1>0
\end{array}\right.\\
\left\lbrace\begin{array}{l}
\left[\begin{array}{l}
x=2\\
x=-1
\end{array}\right.\\
y^2=29-2x\\
x+y+1>0
\end{array}\right.
" alt="\left\lbrace\begin{array}{l}
2^{\log_2(x+y+1)}=x^2+y-1\\
\log_{\sqrt{29}}(y^2+2x)=2
\end{array}\right.\\
\left\lbrace\begin{array}{l}
x+y+1=x^2+y-1\\
x+y+1>0\\
y^2+2x=29
\end{array}\right.\\
\left\lbrace\begin{array}{l}
x^2-x-2=0\\
y^2=29-2x\\
x+y+1>0
\end{array}\right.\\
\left\lbrace\begin{array}{l}
\left[\begin{array}{l}
x=2\\
x=-1
\end{array}\right.\\
y^2=29-2x\\
x+y+1>0
\end{array}\right.
" align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=%5Cleft%5Clbrace%5Cbegin%7Barray%7D%7Bl%7D%0A%5Cleft%5B%5Cbegin%7Barray%7D%7Bl%7D%0Ax%3D2%2C+y%5E2%3D25%5C%5C%0Ax%3D-1%2C+y%5E2%3D31%0A%5Cend%7Barray%7D%5Cright.%5C%5C%0Ax%2By%2B1%3E0%0A%5Cend%7Barray%7D%5Cright.%5C%5C%0A%5Cboxed%7B%28x%2Cy%29%5Cin%5Clbrace%282%2C5%29%2C%28-1%2C%5Csqrt%7B31%7D%29%5Crbrace%7D)
0
\end{array}\right.\\
\boxed{(x,y)\in\lbrace(2,5),(-1,\sqrt{31})\rbrace}" alt="\left\lbrace\begin{array}{l}
\left[\begin{array}{l}
x=2, y^2=25\\
x=-1, y^2=31
\end{array}\right.\\
x+y+1>0
\end{array}\right.\\
\boxed{(x,y)\in\lbrace(2,5),(-1,\sqrt{31})\rbrace}" align="absmiddle" class="latex-formula">